Consumers' perceptions on the service quality in the motor vehicle repair and service industry: an exploratory study in Klang Valley, Malaysia - Abu Bakar, Elistina; Amin, Naemah (Universiti Putra Malaysia Press, 2011)
Motor vehicle repair and service are common and regular services used by consumers in Malaysia. The high demand for these services is contributed by the continued increase in the number of registered vehicles and the number of driving licences issued annually. There are also many complaints reported in the Tribunal for Consumer Claims (TCC) in relation to this industry. Thus, this study aimed to identify the perceptions of consumers towards the quality of the services provided by motor vehicle garages. A total of 400 respondents participated in the study through simple random sampling and data were collected using a self-administered questionnaire. The results of this study indicated that most of the respondents generally had low and moderate perceptions of the service quality. Meanwhile, among the matters that need to be given more considerations are to ensure that the written consent from the consumers is given before undertaking any repair work, and to provide written statements describing the services and the estimated labour fees incurred. Thus, it is recommended that the enforcement bodies enforce the laws strictly and more attention be given to small garages. This study highlighted the seriousness of the problems and it also showed the importance of enacting a specific statute governing this industry in order to achieve a higher standard of services as well as to provide a comprehensive consumer protection.